(untitled) (MAUSAM, 2025)
This study investigates tri-decadal (1991-2022) trends in near-surface and columnar aerosols in two distinct regions of India: the arid region (encompassing Gujarat, Punjab, Haryana, Rajasthan, and Delhi) and the humid Northeast Region (including Meghalaya, Assam, Nagaland, Manipur, Mizoram and Tripura) to comprehend the relation between these aerosols and meteorological parameters in these two regions. By employing satellite reanalysis datasets, including the Indian Monsoon Data Assimilation and Analysis (IMDAA) and the Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA2), the study assesses spatial and temporal variations in aerosol optical depth (AOD) and Ångström Exponent (AE), considering diverse aerosol types such as black carbon, sulfate, dust, and sea salt. Results reveal distinct AOD characteristics between arid and humid regions, with differing medians and variability. Monthly variations highlight distinctive patterns in aerosol concentrations, influenced by both natural sources and anthropogenic activities. Wind speed and direction was investigated with emphasis on how wind circulation patterns elucidate aerosol dispersion, highlighting seasonal influences. Correlation analyses between aerosols and meteorological anomalies reveal negative correlations with precipitation and positive correlations with temperature, indicating aerosol indirect and direct effects, respectively. Continuous Wavelet Transform (CWT) was utilized to assess long-term periodicities of AOD and precipitation over the two regions which are subjected to distinct abundance of rainfall. This study offers a brief insight into the interaction of prevailing aerosols in these environmental settings and the local climate over past three decades with notable distinctions over the two regions.